The Role of the Sahabat Bencana Website in Strengthening Village Resilience: An Analysis of the Utilization of Disaster Information in Forming Disaster-Resilient Villages in Pasaman Barat Regency - Ferdi Wardana; Abdul Wahab; Wadi Murbarok (Yayasan Hisnul Muslim Lombok, 2024)
Indonesia, as the largest archipelagic country in the world, faces significant natural disaster risks due to its geographic location between three major tectonic plates. West Sumatra Province, particularly Pasaman Barat Regency, is a high-risk area for disasters such as flash floods, exacerbated by geographical conditions, high rainfall intensity, and spatial planning violations. This study aims to design and evaluate flood disaster management strategies through the utilization of information from the internet, particularly via the